2020
DOI: 10.3928/23258160-20200831-04
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Primary RRD With and Without Concurrent Full-Thickness Macular Hole (PRO Study Report No. 7)

Abstract: BACKGROUND AND OBJECTIVE: Non-causal macular holes (MHs) can occur concurrently with rhegmatogenous retinal detachments (RRDs). The visual outcomes and surgical approach for these eyes are variable. PATIENTS AND METHODS: This was a multi-institutional, retrospective review of all primary retinal detachment surgeries from January 1, 2015, through December 31, 2015. Pre-, intra-, and postoperative metrics were recorded. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…In contrast, noncausal MH and RRD have been reported to result in significantly worse visual acuity outcomes than RRD without MH. 20 Moreover, our results were not inferior and, in most cases, better than the ones reported in literature without the use of the inverted flap (Table 2 ). For instance, in the more recent published case series by Najafi et al on 17 MH-RRD patients, 15 of whom underwent ILM peeling, only 24% of the patients reached a final BCVA of at least 20/80, and the final MH closure rate was 71%.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, noncausal MH and RRD have been reported to result in significantly worse visual acuity outcomes than RRD without MH. 20 Moreover, our results were not inferior and, in most cases, better than the ones reported in literature without the use of the inverted flap (Table 2 ). For instance, in the more recent published case series by Najafi et al on 17 MH-RRD patients, 15 of whom underwent ILM peeling, only 24% of the patients reached a final BCVA of at least 20/80, and the final MH closure rate was 71%.…”
Section: Discussionsupporting
confidence: 53%
“…However, the MH closure rate varied greatly from 31% to 100%. [1][2][3]5,9,10,13,[18][19][20][21] Although most patients undergo ILM peeling during the initial surgery, the role of ILM peeling remains controversial. Internal limiting membrane peeling in MH is primarily aimed to improve the surgical outcomes by removing any remaining tractional forces across the macular area.…”
Section: Discussionmentioning
confidence: 99%
“…In the group with MHRD, during the primary surgery, ILM peeling was performed in 19 eyes, in which 17 eyes had MH closed;ILM peeling along with hinged single layer ap were performed in 14 eyes, in which According to previous reports, most eyes of MHRD were macula off. 1,2,4,5 Since macula attachment status would affect the pre-and postoperative visual outcome, to make the comparison more meaningful, we only include eyes with macula off RRD both in the study group and control group.…”
Section: Resultsmentioning
confidence: 99%
“…Macular hole coexisting with peripheral break(s) induced rhegmatogenous retinal detachment (RRD+MH) is noted in 1 to 3% of patients 1 5 .The surgical goal has always been to reattach the retina; however, the techniques have evolved from treating the peripheral break(s) only by scleral buckling or vitrectomy to addressing both the peripheral beak(s) and the concomitant macular hole (MH) with vitrectomy and internal limiting membrane (ILM) peeling with or without ILM flap 1 , 2 , 4 . Previous reports showed that patients with RRD+MH had higher chance of proliferative vitreoretinopathy (PVR) 1 , higher reoperation rate and less favorable visual outcome, compared to patients with simple RRD without MH 2 .…”
Section: Introductionmentioning
confidence: 99%